Systematic Observation of Frail Older Patients in Homecare - Implementing a Competence Improvement Program - Torunn Strømme; Ingrid Tjoflåt; Karina Aase (Scandinavian University Press (Universitetsforlaget), 2020)
Background: The early recognition of deterioration in frail older patients is a vital competence of homecare professionals, yet there is a gap between competence demands and actual competence. The aim of this study is therefore to describe and analyse the implementation of a competence improvement program for the systematic observation of frail older patients, developed and implemented in two homecare settings in Norway. Methodology: The study applied a descriptive qualitative design consisting of observation, focus group interviews, and individual interviews. Results: Homecare professionals described the competence improvement program differently both within and across the two homecare districts. They gave diverse explanations for the purpose of the program, most of them involving positive expectations towards improving the current observational practice. The content of the competence improvement program was complex and consisted of multiple components, which the participating homecare professionals experienced as demanding. The process of implementing the competence improvement program was influenced by the difficult flow of information, limited available time, and challenges related to simulation. Conclusion: The implementation of a complex competence improvement program for the systematic observation of frail older patients in homecare requires careful planning with regard to content, process, and context.